Social protection for working-age women in Tanzania: Exploring past policy trajectories and simulating future paths - Roosa Lambin; Milla Nyyssölä; Alexis Bernigaud (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Tanzania has expanded its social protection framework significantly over the past decade, but the country continues to grapple with important gender inequalities. This paper examines, first, the evolution and effects of Tanzania's social protection policies since the 2000s, from the perspective of working-age women. Drawing on a scoping review of diverse evidence, the paper shows that despite progressive legislative reforms and policy efforts to extend social assistance and insurance arrangements, significant inequalities in access to social protection persist for women across the formal and informal sectors. Second, this paper explores, through microsimulations, the potential benefits of introducing a child grant scheme for families as an instrument for gender-responsive social protection expansion. The simulation findings indicate that introducing child grants allocated to the main caregiver has great potential to promote women's empowerment and the achievement of SDGs in Tanzania.
Keywords: J16; I3; I38; C15; 330; social protection; Tanzania; women; gender; microsimulation; social insurance; social assistance